Prediction of growth behavior of thermally grown oxide considering the microstructure characteristics of the top coating. Issue 10 (15th May 2021) - Kim, D.H.; Kim, K.K.; Moon, B.W.; Park, K.B.; Park, S.; Seok, C.S.
Abstract: Under steady-state conditions, the high-temperature oxidation of a thermal barrier coating (TBC) leads to the formation of a thermally grown oxide (TGO). This growth of TGO is a major cause of damage to the TBC, as it results in delamination of the top coating, which decreases the adhesion strength of the bond coating. In this study, an isothermal degradation test was performed to obtain the growth curve of the TGO of a TBC. The growth behavior of the TGO differs with respect to the microstructure of the top coating. Accordingly, if the growth of the TGO can be predicted universally for air plasma-sprayed (APS) TBCs, the time and economic costs can be saved as additional tests would not be required. In this study, a model that can predict capable of predicting the growth of the TGO on an APS TBC with various microstructures. An isothermal degradation test was performed on three specimens featuring substrates and top coatings with different microstructures. The results confirmed that the growth of the TGO was affected by the microstructure of the top coating, regardless of the type of substrate. A structure constant term accounting for the thickness and porosity of the top coating was defined. Furthermore, the reaction rate constant was derived based on the measured TGO thickness. Using these constants, a novel equation for predicting the growth behavior of the TGO with respect to temperature and the microstructure of the top coating was proposed. The validity of this prediction model was verified through comparisons with the previously reported results.